Malta : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Malta during 1995-97. The brisk pace of GDP growth was maintained in 1995-96. However, the strong output growth was accompanied by a sharp deterioration in the external accounts, reflecting, in the main, a decline in national savings, from 27 3/4 percent of GDP in 1992-93 to some 20 percent of GDP in 1995-96. Factors contributing to these developments included a marked loosening in the fiscal stance and accelerated growth in bank lending, linked in part to financial market deregulation and intensified competition among banks.